NILAI PERUSAHAAN: PENGARUH DARI INVESTMENT OPPORTUNITY SET, PERTUMBUHAN LABA, DAN PERTUMBUHAN ASET DIMODERASI UKURAN PERUSAHAAN - Fadhilah, Restu; Zulaecha, Hesty Erviani (STIE Mahardhika, 2026)
This study aims to examine and analyze the influence of Investment Opportunity Set, Growth Potential, and Asset Growth on Company Value using Company Size as a moderating variable. The population for this study consisted of 159 companies. The sampling technique used in this study was purposive sampling with a total sample of 27 companies. The data used is quantitative data and consists of secondary data in the form of annual reports of consumer cyclical sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. This study uses regression analysis and panel data analysis using Eviews version 12 to test the proposed hypothesis and determine the accuracy of the estimation model used. The results of this study indicate that investment opportunity sets have an impact on company value, while revenue growth does not have an impact on company value, and asset growth has an impact on company value. The size of the company can moderate the effect of the investment opportunity set on company value, while the size of the company cannot moderate the effect of revenue growth on company value. and the size of the company can influence the impact on.